2021
DOI: 10.1097/qad.0000000000002987
|View full text |Cite
|
Sign up to set email alerts
|

Microfinance, retention in care, and mortality among patients enrolled in HIV care in East Africa

Abstract: Objective: To measure associations between participation in community-based microfinance groups, retention in HIV care, and death among people with HIV (PWH) in lowresource settings.Design and methods: We prospectively analyzed data from 3609 patients enrolled in an HIV care program in western Kenya. HIV patients who were eligible and chose to participate in a Group Integrated Savings for Health Empowerment (GISHE) microfinance group were matched 1 : 2 on age, sex, year of enrollment in HIV care, and location … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…through nancial assistance. (41)(42)(43) This form of mutual support leads to good results, especially for patients in complex situations, requiring holistic/biopsychosocial care (44).…”
Section: Discussionmentioning
confidence: 99%
“…through nancial assistance. (41)(42)(43) This form of mutual support leads to good results, especially for patients in complex situations, requiring holistic/biopsychosocial care (44).…”
Section: Discussionmentioning
confidence: 99%
“…This form of mutual support leads to good results, especially for patients in complex situations, requiring holistic/biopsychosocial care [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Future HIV prevention programs should prioritize providing opportunities to enhance economic empowerment through offering vocational classes and financial literacy training, as well as creating incomegenerating projects. Economic empowerment support groups have been suggested as an underutilized intervention for both people living with and at risk for HIV in Kenya (Kibicho et al, 2015), and membership in a microfinance group has been shown to be related to improved HIV outcomes in Kenya (Genberg et al, 2021).…”
Section: Economic Empowermentmentioning
confidence: 99%